PERAN MEDIASI MOTIVASI PADA HUBUNGAN SISTEM REWARD TERHADAP KINERJA KARYAWAN (STUDI PADA PERUSAHAAN FINANCE DI KOTA TABANAN) - Muliani, Ni Putu Adi; Sudibya, I Gde Adnyana; Sintaasih, Desak Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study was to determine the mediating role of motivation in relation to the performance of the employee reward system (study at three companies Finance in Tabanan City. This research was conducted in the Federal International Finance (FIF), Adira Finance (Adira) and Summit Oto Finance (OTO) Tabanan Branch is engaged in financing leasing, factoring, consumer financing with technical analysis structural equation modeling (SEM). Through the method with sample slovin of 65 respondents. The results of the analysis concludes reward systems significant positive effect on employee performance. Reward systems significant positive effect on employee motivation. Work motivation significant positive effect on the performance of the company's employees in finance Tabanan City. To increase motivation, reward systems should be as feedback on performance results must be improved, providing a challenging job to be done so that employees always try to give maximum work. Improve performance, as well as increase the personal competence that can be done through compliance with rules and procedures applicable to the company's progress .
Keywords: system of reward, motivation and performance